PENDEKATAN DAN METODE PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Yuliany (Fakultas Agama Islam Universitas Wiralodra, 2022)
The purpose of writing this paper is to analyze the approaches, methods, and techniques of learning Islamic Religious Education. The use of Islamic education methods is how an educator can understand the nature of the method and its relevance to the main goal of Islamic education, namely the formation of a person of faith who is always ready to serve Allah SWT. The conclusion is that educators in the Islamic education process are not only required to master a number of materials that will be given to their students, but they must master various educational methods and techniques for the continuity of transformation and internalization of Islamic Religious Education subjects.